LEGALITY OF DEBT RECOVERY LETTERS WITH THE POWER OF SELLING BASED ON ARTICLE 224 HIR (HERZIEN INLANDSCH REGLEMENT) - Nyoman Chrisna Dewi Asmarani; I Nyoman Sujana; I Nyoman Putu Budiartha (Warmadewa Press, 2019)
This research aims is to determine the basis for judges' considerations in ratifying the sale and purchase deeds based on the Debt Recognition Letter with Power of Attorney to pay off debts in the Decision of the Supreme Court No. 2290 K / PDT / 2012 which can be justified based on the prevailing laws and regulations and knowing the matters that need attention concerning the legal consequences of the deed of selling right for guarantee of Land Rights. This recent study uses a normative legal research method that examines and analyzes existing legal issues through existing legal sources and applicable laws and regulations. The results of this study found that the Judge's Consideration in the Supreme Court Decree No. 2290 K / PDT / 2012 which stated that Judex Facti was not wrong to apply the law, decided two legal actions of the plaintiff were legally valid and the legal consequences that occurred after the Supreme Court Decision No. 2290 K / PDT / 2012, then the creditor can have a Guarantee for Land Based on a Credit Recognition Letter made imperfectly (Authentic and Unilateral) on the basis of a Deed of Sale and Purchase without a number authorized by the Panel of Judges in the Decision.